TLR2 enhances ovarian cancer stem cell self-renewal and promotes tumor repair and recurrence - Chefetz, Ilana (Landes Bioscience, 2013)
Primary ovarian cancer is responsive to treatment, but chemoresistant recurrent disease ensues in majority of patients. Recent compelling evidence demonstrates that a specific population of cancer cells, the cancer stem cells, initiates and sustains tumors. It is therefore possible that this cell population is also responsible for recurrence. We have shown previously that CD44+/MyD88+ epithelial ovarian cancer stem cells (CD44+/MyD88+ EOC stem cells) are responsible for tumor initiation. In this study, we demonstrate that this population drives tumor repair following surgery- and chemotherapy-induced tumor injury. Using in vivo and in vitro models, we also demonstrate that during the process of tumor repair, CD44+/MyD88+ EOC stem cells undergo self-renewal as evidenced by upregulation of stemness-associated genes. More importantly, we show that a pro-inflammatory microenvironment created by the TLR2-MyD88-NFκB pathway supports EOC stem cell-driven repair and self-renewal. Overall, our findings point to a specific cancer cell population, the CD44+/MyD88+ EOC stem cells and a specific pro-inflammatory pathway, the TLR2-MyD88-NFκB pathway, as two of the required players promoting tumor repair, which is associated with enhanced cancer stem cell load. Identification of these key players is the first step in elucidating the steps necessary to prevent recurrence in EOC patients.